PENGELOLAAN BENTENG TUJUH LAPIS DI KECAMATAN TAMBUSAI KABUPATEN ROKAN HULU TAHUN 2012-2014 - Faishal Hadi; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
is an integral part of national development is done in a systematic, integrated, sustainable, and responsible while providing protection against religious values, cultures living in the community, sustainability and environmental quality, as well as the national interest stipulated in the Act No.10 of 2009 on Tourism. As stated also in the vision and mission of Riau Province in 2020. Looking at the condition of Cultural Property in Rokan Hulu are Benteng Tujuh Lapis that need management, in the process there is a barrier for some of the land in this country sites hereditary there are people who live across the region, a problem that too continued in the absence of serious management of the local government which caused this cultural sites almost in name only, then this is the responsibility of local governments in the management of cultural extinction for the site and can be enjoyed by future generations.In this study the authors use the theory as a tool of analysis in this research is the theory of decentralization and local government management. While the approach used in this study is a qualitative approach with descriptive kind, which seeks to analyze the dynamics and explain the data obtained from observations and aim to reinforce and strengthen a theory so as to obtain information about the current situation. Data collection techniques in this research is to use interview techniques, documentation and observation.Results The study authors concluded that the Management Consisting Of the preservation and development of Benteng Tujuh Lapis, Very minimal budget although the Government has formulated the Strategic Plan for Tourism Rokan Hulu , causing Efforts hearts Forms of rescue and restoration is only limited to discourse , Up At The singer is unclear by the Government Subscription Management Fortress seven Layer . Barriers Then Management Benteng Tujuh Lapis Operates internal capabilities that agencies and Human Resources hearts management efforts Fortress Seven Layer yet offset hearts ability Execution because ability Implementation would be more determine the extent of the barriers or acceleration Plans has been prepared can be implemented and operates the external policy of the Government The area yet responded to positively by the 'community relocation policy because deemed not meet choice solution they want.Keywords : Culture, Tourism, Decentralization, Management, And Local Government